Implementasi Teknologi Digital Audio untuk Identifikasi Data Vokal Dalam Pembelajaran Mayor Vokal Pada Prodi PSM: (Celemony Melodyne 5 Untuk Koreksi Data Audio) - pravasta bentar maulany (IAKN Ambon, 2023)
Talking about software or applications in the digital world, can support the learning process and improve the learning atmosphere in the classroom. With the current development of technology and the Internet, many applications or VSTs can be obtained for free on the Internet. One of the VST plugins is Celemony Melodyne 5 which can be used by lecturers to improve the pitch, timing, amplitude, and vibrato of student voices, and other things that can be made with Celemony Melodyne 5. The application of Celemony Melodyne in audio data is in the form of polyphonic data, aiming to review the data like what can be corrected with Melodyne 5 and how it is applied in correcting audio data so that conclusions can be drawn about the source of the audio data that can be used or re-recorded. So it is necessary to describe what happened in the application of Celemony Melodyne 5. This study uses descriptive qualitative research to describe the use of Celemony Melodyne 5 to process and correct audio data that can be corrected and get the final conclusion of what kind of data can be corrected and maintained for further processing.